E-appointment system - Nur Amanina, Zainal (2019)
In today's era, internet usage is widespread throughout the world. Most industries use the online system to access information and other things with internet. The title of this bachelor project is E-Appointment System. The main objective of this system was developed to facilitate University Malaysia Pahang (UMP) students to make an appointment with lecturers. There are various ways for students to make an appointment with lecturers at UMP such as meeting lecturers personally, making phone calls or messages via social networks. However, with this system, appointments are made more organized and recorded for reference. This system is built on the web and is generated using web programming languages such as PHP, HTML and MYSQL as the database for this system. The target user of this system consists of students, lecturers and system administrators. The method or technique used to develop this system is Rapid Application Development (RAD). There are four phases in the RAD which are requirement phase, the design phase, the development phase and the cutover phase. This method is selected because it allows this system to be created within a limited time. In conclusion, this project can save energy, time and reduce operating costs.